IMAM SEBAGAI SERVANT LEADERSHIP - Adinuhgra, Silvester (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
A servant leadership has a distinctive leadership character. The virtue of hisleadership is the growth and prosperity of the people and communities he isin. The strength of his leadership is to place the needs of others first and helppeople grow as high as possible. The leadership character of servant leadershipis inherent in the person of a priest. The Priest has the power of leadershipclosely connected with his identity as an ordained person. The identity ofa priest is a ministerial priesthood that serves the Church and Society. Theleadership of a priest characterized servant leadership is missed by peoplein Meratus mountains. The presence of the shepherd character of servantleadership is a desire to improve the quality of priests and their church life.